Al Shismma's Character as a Justice Seeker and an Avenger in Ahmed Saadawi's Novel "Frankenstein in Baghdad" - Ghazi Mohasien, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The present paper aims to examine and study the monster's character, Al Shismma, that was created from the parts of dead people from the war in Iraq. Saadawi sends many messages throughout his dreadful and supernatural character, such as the misery life and lousy situation in Iraqi society at that time and also the harsh reality and negative side of the war and its consequences on people. Ahmed Saadawi takes the same story of Mary Shelley's Frankenstein monster to describe the terrors of living in the city of Baghdad after the 2003 United States illegal invasion. Saadawi tries to identify the origins of the terrorist activities that have ravaged the country and introduces his "Frankenstein" with a set of issues to strengthen the ordinary tragic consciousness held by the entire structure of the Iraqi community. The character of AL Shismma considers himself the only justice in the earth, and it is his duty that he come for his revenge. He plans to get revenge from all the criminals in Iraqi society and revenge for each part of his body that belongs to the victims of war. The purpose of this paper is to show how Al Shismma transforms his supernatural power and strength to spread justice, help the Iraqi victims, and also get revenge from the criminals of the war. Saadawi represents his abnormal character or monster as the only rescuer in his country and reflects the harsh and tragic life of the Iraqi community during the American invasion.